Human Chorionic Gonadotropin Priming Does Not Improve Pregnancy Outcomes of PCOS-IVM Cycles - Lin, Yihua; Zheng, Xiaoying; Ma, Caihong; Li, Xiaoxue; Zhang, Xinyu; Yang, Puyu; Xu, Jiayu; Zhu, Jinliang (Frontiers in Endocrinology, 2020)
Background: Influence of pre-retrieval human Chorionic Gonadotropin (HCG) priming on outcomes of in vitro maturation (IVM) remains controversial. This study aimed to evaluate the effect of HCG priming before oocyte retrieval on clinical outcomes of IVM cycles in patients with polycystic ovarian syndrome (PCOS). Methods: This was a retrospective cohort study analyzing data from the first IVM cycles of unstimulated PCOS patients in a reproductive center of university affiliated hospital from January 2006 to December 2017. Patients received HCG injection before oocyte retrieval were assigned to HCG priming group and those without HCG administration were categorized as none HCG priming (Non-HCG) group. Main outcomes included oocyte maturation rate, number of embryos available, clinical pregnancy rate and live birth rate. Candidate factors of clinical pregnancy rate was explored by univariate analysis and multivariate logistic regression analysis. Results: There were 324 patients meeting the inclusion and exclusion criteria. Among them 129 women received HCG priming and 195 other did not. Women in HCG group had significantly lower basal FSH level (5.17±1.63 vs 5.80±2.38) than Non-HCG group. Both FSH levels were less than 10IU/L and the absolute difference was 0.63IU/L. Other basic characteristics were similar between groups with or without HCG priming. Oocyte maturation rate was trend to be higher in HCG group (52.68% vs 48.56%) but no statistical significance was found (P=0.097). No significant difference in clinical pregnancy rate was found between HCG and Non-HCG groups (31.37% vs 35.67%). Miscarriage rates (31.25% vs 34.43%) and live birth rates were also similar between groups. HCG priming was not correlated with clinical pregnancy rate in both univariate analysis (P=0.468) and multivariate logistic regression analysis (P=0.538; OR, 1.212; 95%CI, 0.657-2.237). Conclusion: HCG priming before oocyte retrieval may not improve clinical outcomes of IVM in patients with PCOS.